2017
DOI: 10.1080/02699052.2017.1387931
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an intervention programme for rehabilitation of awareness of deficit after acquired brain injury: A pilot study

Abstract: This research provides evidence in favour of the effectiveness of implementing an intervention programme for AD in the context a global rehabilitation process for patients with ABI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The results of the present study are promising and highlight the importance of considering specific intervention programmes in self-awareness, in the context of a broader rehabilitation process. Previous research had demonstrated that specifically tackling this cognitive deficit during rehabilitation is effective at improving self-awareness of patients who had suffered ABI (Lundqvist et al, 2010;Schrijnemaekers et al, 2014;Villalobos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the present study are promising and highlight the importance of considering specific intervention programmes in self-awareness, in the context of a broader rehabilitation process. Previous research had demonstrated that specifically tackling this cognitive deficit during rehabilitation is effective at improving self-awareness of patients who had suffered ABI (Lundqvist et al, 2010;Schrijnemaekers et al, 2014;Villalobos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This specific result suggests that the initial level of self-awareness might be a boundary for achieving meaningful functional outcome enhancements through a specific intervention programme. It seems reasonable that patients with very low initial selfawareness, despite experiencing large improvements in this dimension (Villalobos et al, 2018), were less likely to achieve a significant post-treatment self-awareness level to lead to a meaningful change in functionality. Still, the correlation analyses in the whole group, including those patients who did not undertake the self-awareness programme confirmed that improvements in selfawareness are associated with enhancements in functional outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Awareness of Deficit Scale is a semi-structured scale developed to measure the level of awareness of deficit for a group of patients with acquired brain injury (Villalobos et al, 2018). The scale considers three main areas of awareness: awareness of injury, awareness of deficit and awareness of disability.…”
Section: Tablementioning
confidence: 99%